(3GdCLhHI GdaGNQI Yf GdCSFdI GdaGLQI QOkG Ydi Gdedd GdcGaQI ef bHd Yde GdcdGes - (3CHhGdYHGS TgGH GdOjf CMeO Hf GOQjS Hf YHO GdQMef GdUfgGLj GdbQGaj GdeGdcj,J (B684 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf HYV GdfUGQi bO CfTC QSGdI s
(3BNQgG (B:s
(3hcja jSY Cgd GdcJGH Cf jYJbOhG UMI gPg GdcJH hgPg GdfHhGJ Je GdcJGH hddg GdMeO hGdefg hGdKfGA GdMSf GdLejd hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg s
(3GdfSNI HgG MhGTs
(3QOkG Ydi cJGH eTJed Ydi GdGMJLGL HGdbQBf Ydi UMI ePgH GdfUQGfjI s
(3hgh CQHYI CHhGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds